Evaluation of a rubber nitrile stopper as container-closure system of Gavac® vaccine (2020)
The chosen container-closure systems must be compatible with the preparation for which they are applied throughout their validity period. In the present work, the evaluation of the nitrile rubber stopper (RL8-9-105 / 0) was carried out in substitution of the acrylonitrile rubber stopper (FM84 / 5) as a container-closure system for the Gavac® immunogen. The statistical software Statgraphics® Plus 5.1 was used for data processing. A risk management analysis was carried out by means of a cause and effect diagram, the conformity of this cap with the quality specifications referred to in NP 1078 was determined, the physicochemical characteristics of both caps were compared according to the characteristics manufacturer's quality standard, the effect of placebo on the physical properties of the stopper was determined and the container-closure system using the nitrile rubber stopper was evaluated by means of a tightness test and a sterility test. It was concluded that the RL8-9-105 / 0 nitrile rubber stopper can be used as a container-closure system for the Gavac® immunogen, without affecting its main quality parameters.